1989 World Economic and Financial Surveys : Development in International Exchange and Trade Systems. (World Economic and Financial Surveys; World Economic and Financial Surveys ;, 1989)
This paper summarizes major measures taken in the international exchange and trade systems in 1988 and developments in exchange arrangements and the evolution of exchange rates. The exchange arrangements adopted by members since 1973 cover a broad spectrum of degrees of flexibility, from single-currency pegs to a freely floating system. Most countries have adopted arrangements that fall clearly into one or another of the major categories of the present classification system adopted by the IMF in 1982, and countries with dual markets usually have one market that is clearly more important than the other, which allows accurate classification by major market. Changes in IMF members' arrangements for their currencies during this decade have shown a distinct tendency to move toward more flexible arrangements and away from single-currency pegs, continuing a trend that began in the mid-1970s. A qualitative sense of the significance of the trend toward more flexible arrangements can be conveyed by the degree that world trade is affected by countries adopting different arrangements.